Transformative power of spatial memory: an interdisciplinary approach to space as performance. Issue 1 (15th May 2020) - Palinhos, Jorge; Zeković, Miljana; Žugić, Višnja; Antal, Attila; Dela Cruz, Eric V.
ABSTRACT: 'The Quest: Performing with the Ghost' was an interdisciplinary four-day workshop that took place in the abandoned school of Nova Strašnicka Škola, in Prague, under the aegis of PQ 2019. It was mentored by three architects, two directors and a dramaturg and playwright, sharing different approaches to explore and develop performances based on the specific properties of the space. The workshop was prepared in advance, based on discussions and the sharing of ideas and concepts. Each mentor was allowed to present their approach with the participants and the end result was an interdisciplinary exhibition. This interdisciplinary approach promoted the discussion of different spatial methodologies and raised the awareness of the participants to the different physical, material, sensorial, phenomenological, emotional and performative approaches to space. In this article, we propose to systematize and present some of the different methods employed in the workshop. We will briefly give the theoretical framework of each exercise undertaken by the participants, and discuss their potentialities as tools for exploring, transforming and performing spatial events, allowing space to be seen as a performative agent, an inspiration, a tool or an event.